2021
DOI: 10.1111/jocn.16143
|View full text |Cite
|
Sign up to set email alerts
|

Scoping review: Social support impacts hospital readmission rates

Abstract: Aims and objectives: To review and synthesise the current literature on social support and hospital readmission rates.Background: Hospital readmission rates have not declined significantly since 2010 despite efforts to identify and implement strategies to reduce readmissions. After discharge, patients often report the need for help at home with personal care, medical care and/or transportation. Social factors can positively or negatively affect the transition from hospital to home and the extended recovery per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Therefore, the relevance and representativeness of these social vulnerabilities remains unclear. While it is possible that the SVS does not capture other important social vulnerabilities in our patient population, the domains that are included likely remain relevant, with increasing evidence demonstrating their prevalence and/or their associations with hospital readmissions in heterogeneous, broad, populations 60–63. We also note that in our study, we asked specifically about social vulnerabilities that may be missing from the SVS—no patients felt that additional questions in additional domains were needed.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, the relevance and representativeness of these social vulnerabilities remains unclear. While it is possible that the SVS does not capture other important social vulnerabilities in our patient population, the domains that are included likely remain relevant, with increasing evidence demonstrating their prevalence and/or their associations with hospital readmissions in heterogeneous, broad, populations 60–63. We also note that in our study, we asked specifically about social vulnerabilities that may be missing from the SVS—no patients felt that additional questions in additional domains were needed.…”
Section: Discussionmentioning
confidence: 97%
“…The concept of social support deals with receiving support from the environment and relationships with others. Social support can reduce the incidence of adverse physiological effects and have a positive effect on a person’s physical performance 44 . But there were circumstances in the study that some factors indicated the absence of a suitable support platform.…”
Section: Discussionmentioning
confidence: 99%
“…A brief screening instrument might prove more practical to implement within busy primary care settings to identify individuals with reduced capacity to self-manage who would benefit from accessing additional resources and supports. Screening is a common practice in a variety of medical settings, such as mental health screening ( Lee et al, 2018 ) and social support screening ( Schultz et al, 2022 ). Screening tools can also be used to identify risk factors such as frailty using simple measures such as assessment of gait speed, timed-up-and-go tests, or the PRISMA-7 questionnaire ( Ambagtsheer et al, 2020 ; NICE, 2016 ).…”
Section: Discussionmentioning
confidence: 99%